From “Plain Abe” to Mythical Mr. Lincoln. Constructing various representational modes of a screen icon - Anne-Marie Paquet-Deyris (IdeAs)
The first exercises in Lincoln screen iconography started in the early 1900s, most notably with the tableau shot at the close of Edwin Porter’s 1903 Uncle Tom’s Cabin produced by the Edison Film Company and representing Lincoln freeing a slave, and with Essanay Studios’ 1908 The Life of Abraham Lincoln, a lost print likely to have been the first work featuring Abraham Lincoln’s entire life. These early movies, quite a few of which were never retrieved, whether silent or talking, seem intent on representing the modes of construction of a historical giant. As historian Mark Reinhart underlines “[Lincoln] was a natural subject for ‘moving pictures’ since he had been such a memorable subject for ‘still pictures’”. How then is the Lincoln persona shaped in three central films, D. W. Griffith’s 1930 Abraham Lincoln, John Ford’s celebrated 1939 Young Mr. Lincoln and John Cromwell’s 1940 Abe Lincoln in Illinois which inscribed on screen a certain hagiographic and melodramatic vein and had a long-lasting effect on the inscription of President Lincoln on screen? And how does the spectator relate to the directors’ adaptive strategies and play on the certainty or ambiguity of the historical account?